Moral and Social Values In The Organization of SKO Kenduri In Lolo Small Village, Bukit Kerman District Keinci District - Hariandi, Ahmad; Sipahutar, Monalisa; Simbolon, Betty Era Natalia; Yulizha, Annisa Firda; Fahriansyah, M. Dimas (Journal Research of Social Science, Economics, and Management, 2022)
This research was motivated by the fact that the Sko feast is rarely done, where the Sko feast is no longer held regularly every year. Sometimes a feast is held every 1 or 5 years. The purpose of this study is to find out the moral and social values ??in the implementation of Kenduri Sko in the Lolo Kecil Village Community and to identify the role of traditional stakeholders in the implementation of Kenduri Sko. This type of research is qualitative with a descriptive method. The determination of informants is done by purposive sampling. This type of data consists of primary and secondary data, collected through observation, interviews, and documentation. The results of the study show that the Kenduri Sko ceremony carried out by the people of Lolo Kecil Village from the past until now aims to be grateful to Allah SWT who has bestowed His grace and gifts to the community, both the blessings of the age and sustenance. The role of traditional stakeholders is very important in the Kenduri Sko event which has always invited boys and girls to participate in the Kenduri event. The community of the small lolo village until now still maintains the Kenduri Sko tradition, in this tradition, there are historical values ??of the past, the value of togetherness and fostering respect among residents. Kenduri Sko Community in the area of ??Depati IV (four) Batu Gong Tanah Kurnia can be held annually as local wisdom. Furthermore, the tradition of sko kenduri is maintained and passed on to the younger generation.